Urban Political Ecology: Environmental Imaginary, Governance, and the Non‐Human. Issue 1 (January 2014) - Gabriel, Nate
Abstract Urban political ecology (UPE) has established a firm foothold as urban environments have become increasingly relevant for both academics and for the broader environmental movement. Over the last decade, UPE has established a position that took as its starting point the tightly interwoven status of "socionature", coupling a critical stance on urban environments through a theorization of society in which the "urban" is a distinct historical expression of capitalism. More recently, some in UPE have voiced the concern that this approach places too heavy an emphasis on structural capitalist forces and have begun to reexamine and push further UPE's engagement with post‐structuralism and post‐humanism. This paper explores three such moves: the first is a resurgence in interest in environmental imaginaries; the second is a closer engagement with the extensive literature on urban governance; the last is a new form of engagement with post‐humanism, specifically the theoretical implications of including non‐human agency into accounts of urban political ecologies.